Preoperative endoscopic predictors of severe submucosal fibrosis in colorectal tumors undergoing endoscopic submucosal dissection - Kaosombatwattana, Uayporn (Endosc Int Open, 2019)
Background and study aims  Endoscopic submucosal dissection (ESD) enables en bloc removal of colorectal neoplasms regardless of size. Submucosal fibrosis is a significant factor for technical difficulty and poor outcomes. We assessed the predictive factors for severe submucosal fibrosis and the ESD outcomes. Patients and methods  Patients undergoing ESD from January 2006 to September 2017 were retrospectively reviewed. The degree of submucosal fibrosis was classified into three types: no fibrosis (F0), mild fibrosis (F1), and severe fibrosis (F2). F0 and F1 cases were grouped as non-severe fibrosis for comparison with the severe fibrosis group. Predictors of severe submucosal fibrosis and ESD outcomes were evaluated. Results  ESD was performed in 524 lesions (60 % male; mean age, 67.8 years). Eighty lesions with severe fibrosis (15.3 %) were observed. The overall en bloc resection rate and curative resection rate were 94.3 % and 77.7 %, respectively. Rates of en bloc resection (91.2 % vs. 94.8 %, P  = 0.2) and perforation (7.5 % vs. 5.6 %, P  = 0.45) were no different between severe fibrosis and non-severe fibrosis groups. However, incidences of non-curative resection and low resection speed were significantly higher in the severe fibrosis group. Among protruding lesions, tumor height and volume were significantly greater in the severe counterparts. A diameter ≥ 40 mm, endoscopic finding of the tumor beyond fold, and fold convergence were independent risk factors for severe fibrosis. Conclusions  Severe submucosal fibrosis is a significant risk factor for non-curative resection and a long procedural time. Tumor size and morphology might help to predict the severity of fibrosis.